COVERED IN SOME COLOURS: USE AND MEANING OF PAINT TO ASANTE AND KASSENA NANKANA ETHNICITIES OF GHANA - KQUOFI, STEVE; Antwi, Emmanuel (Advances in Social Sciences Research Journal, 2015)
Cave art stands as a universal artistic heritage, harking to humanity's quest to proliferate reality, as well as live in a colourful ambience. It is logical to reason that, this Palaeolithic evidence of cave painting that occurred over the various continents extended into ancient cultures and subsequent generations the world over. Yet in documenting history of traditional African art, authors hardly delve into the subject of paint. Up to now, far too little attention has been paid to paint and its role in art among traditional Ghanaian ethnicities. This study therefore focused on the two regions of Ashanti (Asante) and Upper East. Using ethnographical, historical and phenomenological methods, 23 respondents were purposively selected and interviewed by snowball. At the end of the study 11 paints and pigments were found as integral to traditional Ghanaian art of ethnicities in these regions. The study revealed unique ways in which these media were sourced and employed as well as the philosophical meanings that underpinned them. The significance of this work is found in its systematic study of paints and pigments, as a contribution to discourse on traditional African art media.